Dose-response relation between exercise duration and cognition - Chang, Y.-K.; Chu, C.-H.; Wang, C.-C.; Wang, Y.-C.; Song, T.-F.; Tsai, C.-L.; Etnier, J. L. (Medicine & Science in Sports & Exercise, 2015)
Purpose: The study aimed to provide evidence-based recommendations for the prescription of a single session of exercise to improve cognitive performance. In particular, the purpose was to determine the dose-response relation between exercise duration and cognitive performance for a moderate-intensity session of aerobic exercise.